Migrasi dan Perkembangan Wilayah Perkotaan dalam Perspektif Pembangunan Berkelanjutan - Siregar, Hilyati Inayah; Harahap, Isnaini; Nawawi, Zuhrinal M (Jurnal Ekonomi-Qu, 2024)
The migration of populations from rural to urban areas has emerged as a profound phenomenon in the economic transformation and settlement patterns of Indonesia. This research aims to analyze the impact of migration on Sustainable Development Goals (SDGs). Conducted as a quantitative study, it examines the influence of migration levels on poverty rates, Human Development Index (HDI), Per Capita Income, and crime rates across provincial regions in Indonesia. The analytical methods employed include simple linear regression and correlation tests. The findings of this research conclude that migration does not significantly affect poverty rates, HDI, Per Capita Income, or crime rates. This article recommends that the government implement policies and concrete measures to achieve more balanced development, thereby reducing the necessity for population migration to other urban centers..